Planned production of agricultural surpluses? - Otto Matzke (Intereconomics, 1975)
In recent times, the EC-Commission has developed the opinion that, contrary to present practice, food for the purpose of aid ought to be produced systematically. From the point of view of development policy, such notions must rouse serious doubts in their soundness, which would be virtually superfluous in the case of food aid drawn from “unplanned” agricultural surpluses.
Keywords: 330; EC